Augmented Reality and intrinsic motivation: a preventive approach to dropout in upper secondary school - Lembo, Luna; Tombolini, Elisabetta; Morsanuto, Stefania (Form@re - Open Journal per la formazione in rete, 2025)
The phenomenon of school dropout represents a significant challenge for educational systems. Research showes that student motivation is a key predictor of school persistence, influencing the quality and continuity of learning processes (Froiland et al., 2016). In this context, Augmented Reality (AR) has emerged as an innovative tool capable of increasing student engagement and motivation (Garzón et al., 2021; Lembo et al., 2023). This paper presents an experimental study conducted with upper secondary school students, aimed at investigating the role of AR in supporting intrinsic motivation. The intervention, implemented through the Merge Cube, revealed significant differences in interest, effort, and perceived pressure, confirming the potential of AR as an innovative teaching strategy and as a preventive approach to school dropout. Realtà aumentata e motivazione intrinseca: approccio preventivo al drop-out nella scuola secondaria di secondo grado. Il fenomeno della dispersione scolastica rappresenta una sfida significativa per i sistemi educativi. La ricerca evidenzia come la motivazione degli studenti sia un predittore fondamentale della persistenza scolastica, influenzando la qualità e la continuità dei processi di apprendimento (Froiland et al., 2016). In quest’ottica, la Realtà Aumentata (AR) si è affermata come uno strumento innovativo, capace di aumentare il coinvolgimento e la motivazione degli studenti (Garzon et al., 2021; Lembo et al., 2023). La presente ricerca sperimentale, condotta con studenti della scuola secondaria di secondo grado, ha indagato il ruolo della Realtà Aumentata nel sostenere la motivazione intrinseca. Tale intervento, tramite Merge Cube, ha evidenziato differenze significative nelle dimensioni di interesse, impegno e pressione percepita, confermando il potenziale dell’AR come strategia didattica innovativa e come approccio preventivo al drop-out scolastico.